Accumulation and Elimination of Enrofloxacin and Ciprofloxacin in Tissues of Shrimp Litopenaeus vannamei under Laboratory and Farm Conditions. (16th June 2012) - Flores-Miranda, Brisa Marisol; Espinosa-Plascencia, Angelica; Gómez-Jiménez, Silvia; López-Zavala, Alonso Alexis; González-Carrillo, Haydé Hayamaí; Bermúdez-Almada, María del Carmen
Abstract : This study aimed to quantify the accumulation and elimination of Enrofloxacin (ENRO) and Ciprofloxacin (CIPRO) in cultivated Litopenaeus vannamei under controlled laboratory and farm conditions. Laboratory- and farm-raised shrimp were given feed supplemented with 200 mg/kg ENRO for 14 days, followed by a 16-day diet without antibiotics. The levels of ENRO and CIPRO were analyzed by High Performance Liquid Chromatography (HPLC). In the laboratory, ENRO concentrations in the muscle and hepatopancreas reached a maximum (C max ) of 0.54 ± 0.26   μ g/g and 3.52 ± 1.9   μ g/g, respectively; C max values for CIPRO in the laboratory were 0.18 ± 0.13   μ g/g (muscle) and 1.05 ± 0.20   μ g/g (hepatopancreas). In farmed shrimp, C max values for ENRO were 0.36 ± 0.17   μ g/g muscle and 1.60 ± 0.82   μ g/g in the hepatopancreas; CIPRO C max values were 0.03 ± 0.02   μ g/g (muscle) and 0.36 ± 0.08   μ g/g (hepatopancreas). Two to fourteen days were necessary to eliminate both antibiotics from muscular tissue and four to more fourteen days for complete elimination of the antibiotics from the hepatopancreas. These results should be considered in terms of minimum concentrations necessary to inhibit Vibrio bacteria to determine whether the current use of this antibiotic is effective in controlling disease.